2014
DOI: 10.3109/01612840.2014.896061
|View full text |Cite
|
Sign up to set email alerts
|

The Cardiometabolic Health Nurse: Physical Health Behaviour Outcomes from a Randomised Controlled Trial

Abstract: To combat the increasingly poor physical health of people with serious mental illness, the position of a cardiometabolic health nurse has been proposed. We recently conducted a 26-week trial in a regional mental health service. This paper describes the background and rationale for the position, presents the outcomes on health behaviours and health behaviour knowledge and attitudes, and offers recommendations for the future direction of the role. We show that a cardiometabolic health nurse can improve the physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 49 publications
(45 reference statements)
0
25
0
Order By: Relevance
“…A specialist nursing position has been proposed as a potential approach to promoting improved physical health care within mental health services. Positions of this kind, while limited in number, have been evaluated positively (Druss et al ; Happell et al ; McKenna et al ), and the attitudes of nurses from mental health services have been favourable (Happell et al ; Happell et al ), becoming more so following the introduction of a position of this type (Happell et al ). However, at this stage the views and opinions of those most closely affected by the inadequacy in physical health care including carers, have not been canvassed.…”
Section: Discussionmentioning
confidence: 99%
“…A specialist nursing position has been proposed as a potential approach to promoting improved physical health care within mental health services. Positions of this kind, while limited in number, have been evaluated positively (Druss et al ; Happell et al ; McKenna et al ), and the attitudes of nurses from mental health services have been favourable (Happell et al ; Happell et al ), becoming more so following the introduction of a position of this type (Happell et al ). However, at this stage the views and opinions of those most closely affected by the inadequacy in physical health care including carers, have not been canvassed.…”
Section: Discussionmentioning
confidence: 99%
“…Several innovations have been proposed for improving rates of metabolic monitoring by mental health nurses. Happell et al (2014) Results: Rates of metabolic monitoring were low in both services. Survey participants expressed positive views towards physical health monitoring and confidence in relating to mental health consumers.…”
Section: Metabolic Syndromementioning
confidence: 97%
“…However, the improvements have occurred against a background of low initial levels of monitoring, the follow-up periods have been short, and the interventions carry the additional cost of establishing the new roles. While the evidence is clear that there is a significant need for practice improvement in the area of physical health care of people with SMI, it is less clear that development of specialist roles such as that proposed by Brunero and Lamont (2009), Happell et al (2014) and Brown et al (2018) is a solution that has long-term sustainability, especially outside larger urban settings. It is also not clear that conceptualizing physical health care as a "specialist" role will support the practice development of the wider body of mental health nurses (Happell et al, 2015).…”
Section: Ta B L E 4 (Continued)mentioning
confidence: 99%
“…Recent studies (e.g. Happell et al, 2014) have demonstrated that dedicated nurse-led roles aimed at improving access to quality primary care result in significant improvements in physical health behaviours and outcomes. The findings of this and other studies would seem to support the implementation of a nurse-led role to coordinate the physical health monitoring and care of people with serious mental illness; however, economic and consumer evaluations are needed to determine the impact on bridging healthcare inequalities.…”
Section: A Potential Solution To An Enduring Problemmentioning
confidence: 99%